A Slice-Traversal Algorithm for Very Large Mapped Volumetric Models. (December 2021) - Youngquist, Jeremy; Sitharam, Meera; Peters, Jörg
Abstract: When the full-scale storing and retrieving of volumetric models is cost prohibitive, intersection queries require intelligent access to pieces generated on demand. To conform to a given curved outer shape without clipping, such models are often the result of a non-linear free-form deformation applied to a geometrically simpler, canonical model. The additional challenge is then to relate the intersection query back to the pieces of the pre-image of the conforming curved model. Motivated by 3D print slice generation of massive mapped material micro-structure, this paper presents an algorithm to traverse a planar slice of a volumetric mapped model that is too large to be treated as an explicit model. The algorithm safely reduces the large-scale slicing problem to many small-scale problems that can be solved by existing slicing techniques. With the pre-image partitioned into boxes, the algorithm activates boxes to generate micro-structure only where the non-linear image of the box can intersect the given plane. Active boxes are intelligently traversed to guarantee both full coverage and minimize a front of active boxes. Highlights: Large volumetric models require intelligent access to pieces generated on demand. Non-linear free-form deformation intersection queries are pulled to the pre-image. The fat front algorithm activates micro-structure only near the slicing plane. Box traversal minimizes storage of a front of active boxes.